PERTUMBUHAN DAN EFISIENSI PAKAN BENIH IKAN GABUS (Channa striata) YANG DIBERI PAKAN BERPROBIOTIK - Anastasya Zwespana; yulisman .; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT Probiotics are live microorganisms that have a beneficial and be able tosurvive in the digestive tract. The  purpose of this research was to know the effectivity of variant probiotics microbes on feed to increase growth, feed efficiency and survival rate of snakehead fry (Channa striata). The research had been conducted in Laboratorium Dasar Perikanan, Departement of Aquaculture, Agriculture Faculty, Sriwijaya University on January until March 2016. The research method used a Completely Randomized Design with four treatments and three replications. The treatments were P1 : without probiotics (control),   P2 (probiotics A ), P3 (probiotics B) and P4 (probiotics C). Parameters that had been observed   were   survival   rate,   growth,   feed   efficiency,   and   water   quality parameters. The result showed that variant of probiotics on feed gave significant effect of survival rate,growth and feed efficiency of snake head (Channa striata) fry. P3 treatment (probiotic feed consisting of microbes Lactobacillus sp., Streptomyces sp.,  Actinomycetes sp., and yeast) gave the highest of survival rate (95%), growth weight (1.72 g) and growth lenght (1.89 cm), and feed efficiency (34.93%).  During  the  research,  water  quality  were  in  tolerance  range  for Snakehead fry (Channa striata) rearing : temperature was 27 – 280C, pH 5.1 – 6.8, dissolved oxygen 3.11 – 5.96 mg.L-1 and ammonia 0.02 – 0.09 mg.L-1.   Key words : Probiotics, Snakehead fry, Fish feed